Metaphoric units expressing the concept of beauty - Tursunoy Yandashova (Research Parks Publishing LLC, 2020)
Every people or nation can have a real name and status in the world with its values, language and culture. The Uzbek language is one of the important values that have raised the Uzbek nation to such a high level. The article discusses metaphorical interpretations of the concept of beauty in Uzbek and English linguistic culture.